The Impact of Blockchain Technology on Farming Efficiency, Transparency, and Sustainability - Al Hussaini, Muzamil Hussain; Niazi, Imran; Munawar, Nousheen; Abbas, Naveed; Amanat, Ishaq (The Indonesian Institute of Science and Technology Research, 2024)
This paper explores the transformative impact of blockchain technology on the agricultural sector, presenting a comprehensive analysis of its multifaceted benefits for farming practices and supply chains. The decentralized ledger system of blockchain is examined in the context of addressing challenges and unlocking new opportunities for stakeholders. Key areas of focus include increasing trust between parties through reliable information about farms, inventories, and contracts; facilitating seamless information sharing across the supply chain by enabling traceability from farm to fork; significantly reducing agricultural transaction costs through intermediary elimination and process automation; simplifying all stages of the agricultural supply chain via streamlined documentation, verification, and quality control; and improving food safety while eliminating counterfeit items through blockchain's capability to ensure authenticity, origin, and quality. This exploration underscores the potential for blockchain to enhance transparency, efficiency, and sustainability in agriculture, thereby reshaping the future of the industry.